Investigation of the effect of the doping order in GaN nanowire p–n junctions grown by molecular-beam epitaxy. (1st December 2020) - Saket, Omar; Wang, Junkang; Amador-Mendez, Nuño; Morassi, Martina; Kunti, Arup; Bayle, Fabien; Collin, Stéphane; Jollivet, Arnaud; Babichev, Andrey; Sodhi, Tanbir; Harmand, Jean-Christophe; Julien, François H; et al.
Abstract: We analyse the electrical and optical properties of single GaN nanowire p–n junctions grown by plasma‐assisted molecular-beam epitaxy using magnesium and silicon as doping sources. Different junction architectures having either a n-base or a p-base structure are compared using optical and electrical analyses. Electron-beam induced current (EBIC) microscopy of the nanowires shows that in the case of a n-base p–n junction the parasitic radial growth enhanced by the magnesium (Mg) doping leads to a mixed axial-radial behaviour with strong wire-to-wire fluctuations of the junction position and shape. By reverting the doping order p-base p–n junctions with a purely axial well-defined structure and a low wire-to-wire dispersion are achieved. The good optical quality of the top n nanowire segment grown on a p-doped stem is preserved. A hole concentration in the p-doped segment exceeding 10 18 cm −3 was extracted from EBIC mapping and photoluminescence analyses. This high concentration is reached without degrading the nanowire morphology.